2018
DOI: 10.1111/cjag.12169
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling determinants of inferred and stated attribute nonattendance: Effects on farmers’ willingness to accept to join agri‐environmental schemes

Abstract: Attribute nonattendance (ANA) has received very little attention in the context of willingness to accept (WTA), although an increasing number of studies analyze the preferences of ecosystem service providers toward incentive‐based schemes. We add to the understanding of ANA behavior by analyzing stated and inferred ANA in a choice experiment investigating farmers’ WTA for participating in agri‐environmental schemes (AES) in southern Spain. We use mixed logit models, following Hess and Hensher for the inferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
(143 reference statements)
1
7
0
1
Order By: Relevance
“…However, monitoring is costly, and the balance between non-compliance and monitoring is often ignored (Vedel et al, 2015). We observed that the monitoring attribute was insignificant in most of the studies indicating that it plays a minor role in farmers' choice of participating in an AES (Greiner, 2016;Rodríguez-Entrena et al, 2019;Villanueva et al, 2015bVillanueva et al, , 2015a. However, only Broch & Vedel (2012) and Vedel et al (2015) observed that monitoring had a significantly negative impact on respondents' utility and led to increased WTA.…”
Section: Prescription Attributesmentioning
confidence: 85%
See 1 more Smart Citation
“…However, monitoring is costly, and the balance between non-compliance and monitoring is often ignored (Vedel et al, 2015). We observed that the monitoring attribute was insignificant in most of the studies indicating that it plays a minor role in farmers' choice of participating in an AES (Greiner, 2016;Rodríguez-Entrena et al, 2019;Villanueva et al, 2015bVillanueva et al, , 2015a. However, only Broch & Vedel (2012) and Vedel et al (2015) observed that monitoring had a significantly negative impact on respondents' utility and led to increased WTA.…”
Section: Prescription Attributesmentioning
confidence: 85%
“…Though 5 out of 34 reviewed studies used this attribute in their CE; however, 4 of these studies use the same set of choice attributes in their CE (Rodríguez-Entrena et al, 2019;Villanueva et al, 2015bVillanueva et al, , 2015a. According to Villanueva et al (2017, p6), this attribute was included in the CE to "explore a hypothetical future implementation of the EFA requisite of the Common Agricultural Policy (CAP) 'green payment' in permanent crops such as olive groves".…”
Section: Ecological Focus Areamentioning
confidence: 99%
“…to still undertake environmental activities in unsubsidised land, although it should be noted that this land was adjacent to subsidised land and likely to have been benefited from this proximity. Having said that, Rodríguez-Entrena et al, (2019) have shown how payments are usually the contract feature that farmers focus most on.…”
Section: Discussionmentioning
confidence: 99%
“…Also, given survey space constraints we gave priority to collecting farm and farmer characteristics and attitudes over attendance to attributes. Although ANA is a topic of increasing concern, the literature is still inconclusive about the impacts of non-attendance on welfare estimates (Kragt, 2013;Rodríguez et al, 2018) as it can reflect both heuristics or preferences (Heidenreich et al, 2018).…”
Section: Discussionmentioning
confidence: 99%